2017
DOI: 10.1007/s10654-017-0228-0
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal and postural changes of blood pressure predict dementia: the Malmö Preventive Project

Abstract: The role of blood pressure (BP) changes in dementia is debatable. We aimed to analyse how resting and postural BP changes relate to incident dementia over a long-term follow-up. In the prospective population-based Malmö Preventive Project, 18,240 study participants (mean age: 45 ± 7 years, 63% male) were examined between 1974 and 1992 with resting and standing BP measurement, and re-examined between 2002 and 2006 at mean age of 68 ± 6 years with resting BP. A total of 428 participants (2.3%) were diagnosed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 35 publications
0
39
0
1
Order By: Relevance
“…Five prospective studies comprised 43 452 participants in total. According to their statistical methods (Cox proportional hazard model or logistic regression model), 4 studies sampled 41 972 participants using Cox proportional hazard model and 1 study used logistic regression model . Thus, 4 studies were analyzed quantitatively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five prospective studies comprised 43 452 participants in total. According to their statistical methods (Cox proportional hazard model or logistic regression model), 4 studies sampled 41 972 participants using Cox proportional hazard model and 1 study used logistic regression model . Thus, 4 studies were analyzed quantitatively.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 4 prospective studies included in meta‐analysis, 3 studies showed that people with OH had a significantly higher prevalence of dementia and 1 study demonstrated a negative result . When pooled, the results showed a positive overall effect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neurobiologically, it has been shown that this orthostatic stress could lead to cerebral hypo‐perfusion and subsequent formation of white matter hyperinsensities, a well known finding in late life depression (LLD). OH is also highly associated with syncope, falls, and overall increased mortality …”
Section: Introductionmentioning
confidence: 99%